TISSUE EXPANDER OR PERMANENT IMPLANT IN IMMEDIATE BREAST RECONSTRUCTION AFTER MASTECTOMY? A SYSTEMATIC REVIEW - Pérez, María Laura Ramos; Mendes, Talita Aparecida Riegas; Oliveira-Junior, Idam de (Mastology, 2026)
Objective: The aim of this study was to evaluate options for tissue expander and permanent implant and know the main indications, complications, effects on adjuvant treatment, impact on quality of life, and cost-effectiveness of each one. Methods: A systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and MetaAnalyses (PRISMA) statement. For the identification of articles on the topic, PubMed, EMBASE, and Cochrane databases were searched from 2000 to 2021, and only English terms were used. The inclusion criteria were as follows: meta-analyses, systematic reviews, randomized or nonrandomized clinical trials, and observational studies. The analysis of the studies was descriptive. Results: The initial search in the databases identified 65 articles, and after reviewing the inclusion criteria, 32 studies were available. According to relevance, 20 studies were excluded due to unavailability of the full text or irrelevance for the study purpose. Twelve articles were included with an average of 1068 patients per study. The studies were heterogeneous with results mostly favorable for reconstruction at a stage with permanent implant. Conclusion: Singlestage breast reconstruction is a promising strategy with acceptable complication rates and the described advantages. Post-mastectomy radiotherapy increases complications. Finally, studies are still heterogeneous, both in terms of methodologies and results, so it is not possible to extrapolate information without bias.